Evidence for Platelet αIIbβ3 Activation despite Elevated Cytosolic cAMP - Riondino, Silvia; Gazzaniga, Pier Paolo; Pulcinelli, Fabio M. (Thrombosis and Haemostasis, 2001)
Cyclic nucleotides, such as cAMP, are known to inhibit the multistep cascade that results in platelet aggregation. In the present study we provide evidence that it is possible to bypass cAMP inhibitory effect on fibrinogen binding site exposure induced by the thromboxane A2 synthetic analogue U46619, the snake venom toxin convulxin, or by the direct PKC activator OAG, by concomitantly activating a Gi-coupled receptor by means of epinephrine or by inducing cytosolic calcium influx by means of ionomycin. In fact, in our study we demonstrate that, in iloprost-treated platelets, the inhibition of both platelet aggregation and fibrinogen binding was overcome by adding epinephrine or ionomycin. To further confirm this, we used the cAMP analogue dibutyryl cAMP and we obtained platelet aggregation in response to U46619, convulxin or OAG plus epinephrine. Moreover, a complete inhibition of platelet aggregation in the presence of high concentrations of cAMP was observed only in the case of U46619, while a small percentage of aggregation persisted when convulxin or OAG were used, due to the small amount of ADP that both convulxin and OAG are able to release.Since PKC inhibition didn’t allow platelet aggregation to occur in response to the concomitant activation of U46619 or convulxin, plus epinephrine or ionomycin, we can conclude that cAMP-induced inhibition of aggregation can be counteracted by the simultaneous activation of PKC in the presence of an activated Gi-coupled receptor or of an induced calcium influx.
Keywords: Platelet aggregation; cAMP; PKC; PLC; G-protein